Sektor Informal dan Kontribusinya dalam Kehidupan Sosial-Ekonomi Warga Kota Kupang - Laurensius P Sayrani (Badan Penelitian dan Pengembangan Daerah Kota Kupang, 2018)
The informal sector has an important role in socio-economic life in Kupang City. The purpose of this study explains: 1) the profile of the informal sector (type, character and endurance) that developed in Kupang City, 2) the economic and political contribution of the informal sector to labor issues in The City of Kupang. This article is based on research in The City of Kupang using the constructivism approach (qualitative method) as the main method supported by the survey method. The results of this study: (1) profile of the informal sector business in Kota Kupang, which is characterized by : a) unskilled, and if it has skills, it is the result of self-learning (trial and error, observation, experience), self-financed and still limited in terms of people's access to government services; b) limited business capital, socially supported, especially from friends and family, loans and limited access to capital for Government Financial Institutions (including banks); c) business location is not settled, simply at their own houses, rented houses and devolved; d) limited employees, no status, not permanent (daily/weekly) and erratic working hours. (2) The contribution of the socio-economic informal sector in The City of Kupang is identified in several functions, including: a) the function of